PERANCANGAN DAN IMPLEMENTASI WEBSITE PERUSAHAAN DI CV RIZQI INTI BUANA - Nanda Jarti; Nofri Yudi Arifin; Deo Bagus Prayoga (LPPM Universitas Ibnu Sina, 2026)
CV Rizqi Inti Buana still conducts promotion and information dissemination through conventional media such as WhatsApp and limited business networks, resulting in a narrow information reach and making it difficult for the company to compete with competitors who have already utilized digital platforms. The company profile is also still in the form of static files, making access to information for prospective clients less effective. This study aims to design and implement a company website as a medium for digital promotion and information delivery. The method used is the waterfall system development method with modeling using Unified Modeling Language (UML) and database-based design. The results of the study produced a system design consisting of four UML diagrams and thirteen database tables that were implemented into a company website. Testing was conducted in both a localhost environment and an online system at https://rib-batam.com/ using black-box testing, which showed that the system functions properly. The developed website helps the company expand its promotional reach and enables clients to directly access company profile and activity information more easily.